Aerosol infrared stealth technology: Theory and development of infrared suppression and particle dispersion in aircraft plume. (1st March 2023) - Sun, Wen-jing; Gao, Qi-hong; Zhang, Jing-zhou; Hu, Feng; Shan, Yong
Highlights: Expounding the theory and its characters of IR extinction for a discrete particle. Identifying the influences of aerosol injected parameters on the IR suppression effect. Illustrating the distribution characteristics of aerosol clusters in high-speed non-isothermal flow. Abstract: Aerosol infrared stealth technology (AIRST) is a highly effective method to suppress the strong infrared (IR) signal and interfere in the IR detection within a short time. It has been equipped on many low-speed vehicles, such as tanks and helicopters. The researchers have conducted many experimental and numerical investigations on the AIRST applied in the jet engine. The recent two decades have witnessed the rapid development of the particle IR extinction and aerosol IR suppression in aircraft plume. This paper has reviewed the published studies about the AIRST comprehensively, including the IR extinction of a discrete particle, IR radiation suppression characteristics of aerosol clusters, and distribution patterns of aerosol particles. The widely applied theories of particle IR extinction and its applicability have been analysed, as well as the characteristics and influence factors of the particle IR extinction. This paper has summarized the mostly used calculation model for IR transmittance of aerosol particle clusters and the IR suppression characteristics of aerosol particles in aircraft plume. In addition, the effects of aerosol injection on the aerosol particle dispersion and turbulent flow features have been systematically displayed. Finally, the future challenges and suggestions about the AIRST are discussed, which could be valuable for the aerosol IR suppression and its application on the supersonic aircrafts.